The Influence of Popular Culture Icons on Heri Dono’s Visual Art - Mauludya, Oky; Prasojo Yulistianto (JOMANTARA, 2026)
The topic of Popular culture icons in Heri Dono’s works are essentially not merely depictions or normative representations of characters, but rather spaces where principles and ideologies clash. The simplification of communication forms in response to phenomena is thoroughly woven into symbols and traditional values, serving as a form of resistance against the repressive dominance of global culture. Aesthetic leaps and breakthroughs in the creative ideas are presented through humanistic metaphors, functioning as responses to actual phenomena such as politics, culture, and social issues. These elements seem to lead us into a certain reality and guide us toward a particular perception.